A keresztezés eredményre gyakorolt hatása az Észak-alföldi Régió árutermelő juhászataiban - Cehla, Béla (Közép-Európai Közlemények, 2011)
The present problems of the Hungarian sheep farms may be classified in three fields from the point of view of sustainability. The first field is the social problems, the second one is economic and market problems, and the third group contains environmental problems. In my investigation, within the economic problems I dealt with the unfavourable breed structure, which considerably contributes to the low yields typical to Hungary nowadays. For solving the problem, improving the production and breed structure may be a specific objective. Its expected results are developing breeding programs and growing yields. The effect of crossbreeding, being one of the several possibilities of increasing yields as a separately activity, on the economic result were investigated. A calculation model was constructed, which made the effect of the change of input data calculable for the operation of the modeled farm producing for the market. The modeling reflected the improving effect of the crossbreeding on the results. The effect of crossbreeding was modeled on the basis of input prices of the year 2009 in case of farms of 5, 10, 20 and 30 ESU. When preparing scenarios, the natural input data of the model was changed on the basis of results of previous researches, such as yield, weight gain, feed conversion, milk producing ability of ewes; that is every feature influencing the production which is changed by the effect of crossbreeding. The positive effects of crossbreeding were evaluated. Other factors (other input parameters) were not changed during running the scenarios. Sheep farms of every firm size in Hungary may reach positive results only by profit supplement-ing subsidies. In this way it was a relevant issue of my calculation that whether only crossbreeding may result in an extra yield, by which the Hungarian sheep production for the market may be viable, even without profit supplementing subsidies.